Development of a conjugated polyaniline incorporated electrospun poly(vinylidene fluoride‐co‐hexafluoropropylene) composite membrane electrolyte for high performance dye‐sensitized solar cells. Issue 45 (21st August 2015) - Elayappan, Vijayakumar; Murugadoss, Vignesh; Angaiah, Subramania; Fei, Zhaofu; Dyson, Paul J.
ABSTRACT Different weight percentage (2, 3, 4, and 5 wt %) of polyaniline (PANI) were incorporated into electrospun poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVdF‐HFP) composite membranes (esCPMs). The regular morphology, molecular structure, crystallinity, porosity, electrolyte uptake, and leakage of the composite membranes were examined. The esCPMs were activated in liquid electrolyte containing 0.5 M LiI, 0.05 M I2, and 0.5 M 4‐tert‐butylpyridine and 0.5 M 1‐butyl‐3‐methylimidazoliun iodide in acetonitrile to afford electrospun PVdF‐HFP/PANI composite membrane electrolytes (esCPMEs). The influence of different wt % of PANI on the esCPMEs was studied by electrochemical impedance measurements and Tafel polarization studies. The photovoltaic performance of a dye‐sensitized solar cell assembled using 3 wt % PANI incorporated esCPME exhibits a higher power conversion efficiency of 7.20% than that assembled using esPME (η = 6.42%). © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42777.